Implementation of the theory of planned behavior to testicular self-examination among young men in Tehran - Azam Mohamadloo; Fatemeh Mohamadloo (Shahid Beheshti University of Medical Sciences, 2017)
Background: Testicular Cancer (TC) is the most common cancer among men between 20 and 40 years old. Treatment for TC is highly effective when detected before the metastatic stage. Although screening of TC through self-examination is recommended, it seems that many men do not do self-examination routinely, so the current study aimed to evaluate the Theory of Planned Behavior (TPB) as a framework for considering Testicular Self-Examination (TSE) intention among a sample of 20- to 34-year-old men.   Methods: A cross-sectional study was designed and 50 young men were randomly selected. A questionnaire was administered to young men, referring to one of the hospitals in Tehran in 2016. The data were analyzed using SPSS software 16 (SPSS Inc., Chicago, IL, USA), running descriptive tests, chi-square, Pearson correlation, and linear regression analysis.   Results: Mean (SD) age of participants was 30 (3.77) years old. The majority were married (29), followed by single (19), divorced (2).  The correlation tests showed a statistically significant relationship between self-efficacy with intention (P<0.001, r=0.585) and PBC (P=0.006, r=0.359). In a linear regression analysis, TPB components could predict 36.4% of the variance in TSE intention and self-efﬁcacy was found to be the independent predictor of TSE intention (P<0.001, β=0.55).   Conclusion: The structures of TPB might be useful for increasing TSE. So, educational interventions based on TPB could be effective for the primary prevention of testicular cancer.